PERAN PERILAKU INDIVIDU TERHADAP ORGANISASI : TELAAH JURNAL ILMIAH - Ridho, Fadhel A; Saputra, M Febri Rendra; Prayoga, M Dani; Fadillah, Rizal; Anjarwati, Prisca E; Antari, Kholip (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 2 No 03 (2023): EDISI OKTOBER - JANUARI, 2023)
The problem in the role of individual behavior towards the organization is related to understanding human nature, approaches to understanding human nature. The purpose of this research is to answer the question about how the role of individual behavior towards the organization. This study applies the Systematic Literature Review method. Based on the results of a systematic literature review, the researcher found 23 articles which were then filtered into 3 selected articles to be analyzed descriptively. The findings show that what makes up an organization is every individual's behavior that has contributed to the organization. Individual behavior has played an important role in an organization